Toksisitas Abu Terbang Kayu terhadap Nilaparvata lugens dan Kompleks Predatornya - Fransiscus Xaverius Wagiman; Hafiz Fauzana; Kartika Yoga Prasetyani (Jurnal Perlindungan Tanaman Indonesia, 2011)
The brown planthopper (Nilaparvata lugens) is currently a very noxious pest insect and it threatened the self sufficience of rice in Indonesia. Innovation of control technology is urgently needed to be developed. Objective of the study was to determine mortality-effect of the wood fly-ash obtained from pulp factory in Riau against N. lugens and its predator complex. A bioassay of the wood fly-ash was done in the laboratory to determine its activity against the test insects. A randomized complete block design (RCBD) experiment with three treatments —fly-ash 40 kg/ha, botanical insecticide containing of root extract of Derris eliptica, and control— with five replications was conducted at a paddy field in Sleman District Yogyakarta. Results showed that the wood fly-ash was toxic against N. lugens: LD50 at 72 hours after treatment were 4.84 and 43.26 g/m2, respectively. As compared with control and botanical insecticide of D. eliptica, the wood fly-ash was significantly more effective for controlling the N. lugens but relatively safe against predator complex. Dusting of the wood fly-ash at rate of 40 kg/ha effectively reduced population of N. lugens within 2 days but did not significantly reduce population of the predator complex namely spiders (Lycosa sp., Oxyopes sp., Callitrichia sp., Argiope sp., and Tetragnatha sp.), Coccinellidae (Menochilus sexmaculatus and Verania sp.), Cicindelidae (Ophionea sp.), and Staphylinidae (Paederus fuscipes).